Poems on Instagram: verbivocovisual reading in high school classes - Garcia, Stéfany de Souza Campos; Rosário, Flávia Gualberto da Rosa; Passos, Lucas da Silva (The ESPecialist, 2025)
This article seeks to work on the reading of poems in the Instagram social network environment and their reception by readers in high school classes. For this, we consider the notion of the poem as an icon (Pignatari, 1979) in its verbivocovisual dimension, since, in addition to verbal language, poems are born and constituted over time for vocal performance, bringing a textual body that transcends symbolic representation. Considering the experimentation of digital literature, we tried to work with the students on how reading poems on the web is part of a literary tradition that conceives of the poem as a presentification of the word, with the use of images, sounds, the exploration of different media and the work with verse that produces a new language, which is nevertheless still the language of everyday life. We also approached the concept of digital scenography proposed by Maingueneau (2017) to analyze the dimensions of the poem in its configurations for the web. The methodology used was qualitative research with participant observation (Gil, 2021). To this end, a didactic sequence (Dolz, 2004) was carried out that worked on the reading of poems by Sérgio Vaz, João Doederlein and Luca Brandão, which use Instagram as a support. The sequence of activities was developed with third grade high school students from two state schools, since young people are increasingly reading poems published on social networks, interacting in unique ways with the authors. In this sense, we hope to reflect on how the conditions of communication on the internet have reinvented ways of reading poems, taking into account the different dispositions that the text can present on Instagram.